Optical, electrical and morphological study of PEDOT:PSS single layers spiral-bar coated with various secondary doping solvents - Syrový, Tomáš; Janíček, Petr; Mistrík, Jan; Pálka, Karel; Hawlová, Petra; Kubáč, Lubomír; Gunde, Marta (My University, 2017)
The electrical, morphological and optical properties of a series of spiral-bar coated single layers of PEDOT:PSS influenced by the addition of 10 different secondary dopants have been studied. The optical properties of these samples have been analyzed over a broad spectral range from 190 nm to 30 microm using spectroscopic ellipsometry and transmittance. The isotropic model fits the ellipsometric data quite well. No substantial differences in the optical constants were obtained, despite a difference being expected from the significant change of specific electrical conductivity (by 3 orders of magnitude). In the infrared part of spectra, the multiple Lorentz oscillators’ model was used instead of the frequently used Drude model by applying narrow oscillators for molecular vibrations together with the broad oscillators describing electronic transitions in the mid-gap states. The geometrical parameters obtained from ellipsometry evaluation have been found to be in good agreement with standard mechanical characterization probes (profilometry and AFM). The highest value of the specific electric conductivity, 78.3 S/cm, was achieved by using n-methyl methanamide as a secondary dopant. The research results confirm that spectroscopic ellipsometry is a valuable tool for characterization of the functional layers used in printed electronics.
Studium optických, elektrických a morfologických vlastností tenkých vrstev PEDOT:PSS připravených s různými sekundárními dopanty metodou spiral-bar
Keywords: PEDOT:PSS; secondary dopants; spiral-bar coating; spectroscopic ellipsometry; electrical properties; morphological properties; PEDOT:PSS; sekundární dopanty; spiral-bar; spektroskopická elipsometrie; elektrické vlastnosti; morfologické vlastnosti